Terahertz all-optical NOR and AND logic gates based on 2D photonic crystals - Parandin, Fariborz; Karkhanehchi, Mohammad Mehdi (Superlattices and microstructures, 2017)
Usually, photonic crystals are used in designing optical logic gates. This study focuses on the design and simulation of an all optical NOR and AND logic gates based on two dimensional photonic crystals. The simplicity of the proposed structure is a characteristic feature of this designation. Finite Difference Time Domain (FDTD) as well as Plane Wave Expansion (PWE) methods have been used for this structural analysis. The simulation results revealed an increase in the interval between “zero” and “one” logic levels. Also, the simple structure and its small size demonstrate the usefulness of this structure in optical integrated circuits. The proposed optical gates can operate with a bit rate of about 1.54 Tbit/s. •Optical logic gates are a suitable basis for design of optical integrated circuits.•In this study, an all optical NOR and AND logic gates based on 2D photonic crystals was designed.•The proposed structure has a small size, high contrast ratio, high bit rate and low time delay.